WORK-LIFE BALANCE AND TEACHER ENGAGEMENT IN PRIVATE SENIOR SECONDARY SCHOOLS IN RIVERS STATE, NIGERIA (Isagoge - Journal of Humanities and Social Sciences, 2021)
This study examined work-life balance and teacher engagement in private secondary schools in Rivers State. Three research questions and three hypotheses guided the study. The study adopted a correlation research design with a population of 7,143 teachers (2,676 males and 4,467 females) in all the 275 private secondary schools in Rivers State.  The sample size of 714 teachers was drawn through proportionate stratified random sampling technique, which represents 10% of the population. Two self-designed instruments entitled: “Work-life Balance Questionnaire (WLBQ)” and “Teacher Engagement Questionnaire (TEQ)” were used for data collection. The instruments were in two sections – A and B. Section A consisted of the demographic factors while Section B contained the variables that were used to elicit information from the respondents. The Section B contained 20 items on Work-life Balance and 15 items on Teacher Engagement respectively. Face and content validities were ensured by experts in the relevant areas. The Cronbach’s Alpha reliability method was used to establish the internal consistency, and indexes of .79 for WLBQ and .83 for TEQ were established respectively. Research questions 1 and 2 were answered using simple regression while research question 3 was answered using multiple regression. Hypotheses 1 and 2 were tested with t-test associated with simple regression while hypothesis 3 was tested using ANOVA associated with multiple regression at 0.05 alpha level. The findings of the study revealed, among others, that work-life balance significantly and jointly predicted teacher engagement to a very low extent in secondary schools in Rivers State. Based on the findings, it was recommended, among others, that both employers and school managers should create flexible work environments that promote work-life balance for teachers so as to motivate them to perform optimally for the attainment of the educational goals.